1983
DOI: 10.1111/j.1469-8137.1983.tb03506.x
|View full text |Cite
|
Sign up to set email alerts
|

HYPHAL UPTAKE AND TRANSPORT OF NITROGEN FROM TWO 15N‐LABELLED SOURCES BY GLOMUS MOSSEAE, A VESICULAR‐ARBUSCULAR MYCORRHIZAL FUNGUS *

Abstract: SUMMARY Celery (Apium graveolens L.) plants were grown in pots in which the root system was separated from the soil in a side chamber by a fine mesh screen. The side chamber was treated with either an organic (ground plant tissue) or inorganic [(NH4)2SO4] source of 15N. Mycorrhizal (Glomus mosseae) and control (non‐mycorrhizal) plants were exposed to 15N over a period of 30 days (inorganic‐15N) or 88 days (organic‐16N). Mycorrhizal and control plants did not differ in shoot dry weight or shoot P content. Dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
169
2
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(196 citation statements)
references
References 31 publications
23
169
2
2
Order By: Relevance
“…However, some values were sufficiently high (7-8 % in glutamate) to suggest strongly that the external hyphae absorbed and assimilated the supplied ^"NOg^-N. These findings are supported by studies demonstrating that external hyphae of AM fungi are able to take up soil mineral N, both as NH,+-N (Ames et al, 1983;Johansen et al, 1992;Frey & Schuepp., 1993) and as NOg'-N (Johansen et al, 1993;Tobar et al, 1994), and translocate it towards the host plant. However, in these studies it was not clear whether the absorbed N was assimilated into organic compounds or translocated in inorganic form.…”
Section: Discussionsupporting
confidence: 73%
“…However, some values were sufficiently high (7-8 % in glutamate) to suggest strongly that the external hyphae absorbed and assimilated the supplied ^"NOg^-N. These findings are supported by studies demonstrating that external hyphae of AM fungi are able to take up soil mineral N, both as NH,+-N (Ames et al, 1983;Johansen et al, 1992;Frey & Schuepp., 1993) and as NOg'-N (Johansen et al, 1993;Tobar et al, 1994), and translocate it towards the host plant. However, in these studies it was not clear whether the absorbed N was assimilated into organic compounds or translocated in inorganic form.…”
Section: Discussionsupporting
confidence: 73%
“…Using a PTFE membrane between the root compartment and hyphal compartment as a barrier to mobile ions, almost identical results were obtained in a simultaneously conducted experiment with maize (Zea mays) colonized by Glomus intraradices (Frey et al, 1998). Similar findings have been reported previously by Ames et al (1983), Johansen et al (1992Johansen et al ( , 1993Johansen et al ( , 1994Johansen et al ( , 1996, Frey & Schu$ epp (1993) and Tobar et al (1994). At a high N fertilizer concentration, the AMF-mediated transport of "&N from the hyphal compartment was reduced, as also observed by Johansen et al (1994).…”
Section: supporting
confidence: 77%
“…Vesicles are thought to be important storage organs (Smith & Read, 1997) but the reason they were so closely linked to N capture from the patch in this study is unclear, particularly as most of the N captured from the patch was detected in the shoots rather than in the roots. Ames et al (1983) reported that uptake of N (supplied as ("&NH % ) # SO % ) by Apium graveolens was related to the percentage of root length colonized by G. mosseae. However, in this study, the apparent relationship with percentage RLC and patch N capture was an artefact caused by an increase in both these parameters with time.…”
Section: Plant Nitrogen Capture From the Organic Patchmentioning
confidence: 99%